(untitled) (Al-Qamar, 2025)
This article explores the family life of Prophet Muhammad (Peace Be upon Him) as a father, son, and husband, and examines its relevance to modern family systems. Using a qualitative and analytical approach, the study highlights how the Prophet’s conduct within the family provides a comprehensive model for emotional intelligence, ethical leadership, and balanced interpersonal relationships as a son, Prophet Muhammad (PBUH) demonstrated deep respect, gratitude, and loyalty toward his elders, particularly his uncle Abu Talib, ecting values of filial piety and moral responsibility. As a husband, he exemplified compassion, mutual respect, emotional support, and justice, emphasizing partnership rather than authority-based dominance. His interactions with his wives illustrate effective communication, patience, and acknowledgment of women’s rights-principles highly relevant to contemporary marital life. As a father, he showed affection, mercy, and active involvement in the upbringing of children, challenging rigid and emotionally distant parenting norms still prevalent in many societies. The study argues that the Prophet’s family life offers a timeless framework adaptable to modern challenges such as work-life balance, gender roles, parenting stress, and emotional disconnection with in families. By integrating prophet teaching into contemporary family discouse, this research concludes that Islamic family ethics can contribute meaningfully to healthier, more compassionate, and stable family structures in the modern world